2009
DOI: 10.1002/crat.200900289
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetism of manganese‐doped ZnO powder samples

Abstract: The magnetic and structural properties of manganese-doped ZnO powder samples prepared by a solid state method are reported. Magnetization measurements indicate ferromagnetic behavior, with hysteresis observed in the M vs. H behavior at 300 K. Coercive fields were <100 Oe at 300 K. Temperature-dependent magnetization measurements showed evidence for ordering temperatures of >300 K. However, the results show that ferromagnetism originates from the doped matrix rather than any type of magnetic cluster and the fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Additionally, it was observed that, as temperature increases, the peak of the diffractograms of the sample becomes sharper and narrow, thus width decreases. This type of result has also been reported by [36], [37]. The general trend in peak positions, is that as temperature increases, there is a corresponding increase in peak positions.…”
Section: Peak Positioningsupporting
confidence: 85%
“…Additionally, it was observed that, as temperature increases, the peak of the diffractograms of the sample becomes sharper and narrow, thus width decreases. This type of result has also been reported by [36], [37]. The general trend in peak positions, is that as temperature increases, there is a corresponding increase in peak positions.…”
Section: Peak Positioningsupporting
confidence: 85%